Avoiding Complications of the Middle Vault in Rhinoplasty - Pearlman, Steven; Baratelli, Roxana (Facial Plastic Surgery, 2012)
Functional and aesthetic abnormalities of the middle nasal vault are frequent reasons for seeking revision rhinoplasty. Complications in rhinoplasties are inevitable; understanding their etiology can help reduce their occurrence. We will examine the more common sequelae, likely causes, and predisposing factors as well as strategies for prevention.
Keywords: revision rhinoplasty; internal nasal valve; spreader grafts; pollybeak deformity; prevention